Higher G allele frequency of RET C2307t>G polymorphism in female patients with Hirschsprung disease in Yogyakarta, Indonesia - Ahmad Hamim Sadewa; Saryono Saryono; Rochadi Rochadi; Wiryatun Lestariana; Wayan T Artama (Indonesian Pediatric Society, 2008)
Background Hirschsprung disease (HSCR) is a heterogenouscongenital disorder and the current research show that the RETgene is a major locus involved in its pathogenesis. However,whether these genes take a part in sporadically Indonesian HSCRhave not been fully understood.Objective The aim of this study was to analyze the association ofRET gene c2307T>G polymorphism among HSCR patient inYogyakarta population.Methods Genomic DNA was extracted from bowel tissues of 34patients with sporadic HSCR which were removed by surgery ascase group and blood DNA from 46 healthy persons as controlgroup without history of genetic disorder. Exon 13 of RET genewas amplified by polymerase chain reaction (PCR) and wasanalyzed by restriction fragment length polymorphism (RFLP).Results Of 34 patients, 22 were males and 12 were females, givingmale to female ratio of 1.83:1. The c2307T>G polymorphism inRET exon 13 was not significantly difference between patientand control group (chi-square test P=0.17). However, there wasa significant difference in female patient compare with control(chi-square test P=0,04).Conclusion The RET gene c2307T>G polymorphism was foundamong HSCR patient in Yogyakarta population. This poly-morphism can be used as predictor for development of HSCRamong female individual.